Effect of blockage-heat source distance on maximum temperature of buoyancy-induced smoke flow beneath ceiling in a longitudinal ventilated tunnel. (June 2017) - Tang, F.; Cao, Z.L.; Chen, Q.; Meng, N.; Wang, Q.; Fan, C.G.
Highlights: Smoke flow experiments were carried out in a 66 m long model-scale tunnel. Maximum temperature under tunnel ceiling with blockage effect was considered. The factor of different blockage–heat source distance including 0 m is considered. A global model was built and correlated well the measured data. Abstract: Longitudinal ventilation is the commonly mode in tunnel for smoke control. This paper presents experimental study on the effect of blockage-heat source distance on maximum temperature of buoyancy-induced smoke flow beneath tunnel ceiling in a ventilated tunnel. Experiments were carried out in a scale model tunnel with a blockage placed at different position upstream of the fire source. The temperature beneath the tunnel ceiling is measured by K-type thermocouples considering different heat release rate and longitudinal ventilation velocity. Results show that Li model can well predict the experimental data when there is no blockage in the tunnel. With upstream blockage of the heat source and different blockage-heat source distance D considered, including D = 0 m, the maximum temperature beneath the tunnel ceiling first increases to the maximum value when the blockage-heat source distance D = 0.5 m, then decreases as blockage-heat source distance increases. An empirical model including blockage-heat source distance (from 0 m to infinity) is proposed and verified to well collapse and predict the experimental values.